2021
DOI: 10.22373/ej.v8i2.7529
|View full text |Cite
|
Sign up to set email alerts
|

Auditory and kinaesthetic learning styles and L2 achievement: A correlational study

Abstract: This study investigated undergraduate non-English major university students’ auditory and kinaesthetic learning styles and their relationships to second language (L2) achievement in English. It was conducted to resolve the conflicting findings in the literature on the directions and strength of the relationships between learners’ learning styles and their achievements and to investigate the field in relatively under-researched Indonesian participants. The study used a survey as the method of data collection an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
1
0
2
Order By: Relevance
“…Mereka juga cenderung menghasilkan nota dalam bentuk peta minda. Menurut kajian yang dijalankan oleh Masela & Subekti [32], mereka mendapati bahawa murid yang memiliki kecenderungan gaya pembelajaran visual ini gemar dan selesa belajar di dalam kelas yang mana guru menggunakan pelbagai bahan dalam bentuk visual. Prestasi keputusan peperiksaan mereka juga tinggi kerana mereka lebih mudah memahami pengajaran guru yang dizahirkan dalam bentuk visual.…”
Section: Visualunclassified
“…Mereka juga cenderung menghasilkan nota dalam bentuk peta minda. Menurut kajian yang dijalankan oleh Masela & Subekti [32], mereka mendapati bahawa murid yang memiliki kecenderungan gaya pembelajaran visual ini gemar dan selesa belajar di dalam kelas yang mana guru menggunakan pelbagai bahan dalam bentuk visual. Prestasi keputusan peperiksaan mereka juga tinggi kerana mereka lebih mudah memahami pengajaran guru yang dizahirkan dalam bentuk visual.…”
Section: Visualunclassified
“…VAK theorists believe that learning will be effective with regard learning styles and utilize the potential of learners. Previous investigations revealed that the VAK model is appropriate to improve writing skills (Masela & Subekti, 2021;Kusumawarti, Subiyantoro, & Rukayah, 2020;Sabarun, Hamidah, & Marsiah, 2020;Aliakbari & Tazik, 2019;Ramadian, Cahyono, & Suryati, 2019;Foroozandehfar & Khalili, 2019;Setyoningsih, 2019;Rahmawati, Cahyono, & Anugerahwati, 2018;Pratama, Rahmawati, & Irfani, 2017;Tyas & Safitri, 2017;Kayalar & Kayalar, 2017;Rahayu, Riyana, & Silvana, 2017;Balci, 2017;Kazemi, Mahdavi-Zafarghand, & Tahriri, 2016;Rambe, 2014). While some scholars have investigated learners' learning style preference in L2 writing, only limited attention has been given on learning style involving writing strategy in writing an argumentative essay as a basis for analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Gaya belajar merujuk pada preferensi individu dalam menerima, memproses, dan mengolah informasi (Masela & Subekti, 2021). Beberapa siswa lebih nyaman dengan pendekatan visual, sementara yang lain lebih merespons melalui pendengaran atau tindakan fisik.…”
unclassified